Derogacja zasad konkurencji wobec przedsiębiorstw zobowiązanych do świadczenia usług w ogólnym interesie gospodarczym a zasada proporcjonalności: [Derogation of competition rules for undertakings entrusted with the operation of services of general economic interest and the principle of proportionality] (Studia Prawnicze / The Legal Studies, 2011)
Usługi świadczone w ogólnym interesie gospodarczym (Services of General Economic Interest) stanowią jedną z „wspólnych wartości Unii” przyczyniając się do wspierania jej „spójności społecznej i terytorialnej”. Czym zatem są usługi należące do tej szczególnej kategorii wskazanej w art. 106 ust. 2 Traktatu o Funkcjonowaniu Unii Europejskiej (TFUE)? Są to usługi, które charakteryzują się dwoma podstawowymi elementami; służą interesowi ogólnemu (general interest) oraz mają charakter gospodarczy.  The model of regulatory framework for Services of General Economic Interest (SGEI) is a pivotal point in a Europe-wide political and legal debate of liberalisation versus welfare interests. The principle of proportionality is wellestablished is acquis communautaire. It requires each measure taken by the EU legislator to be based on a fair assessment and balancing of interests, as well as on a reasonable choice of means. Article 106 (2) TFEU allows the Member States to exclude certain services from the scope of the Treaty Rules. It could be perceived as a shield for public service against demands of highly competitive, liberalised market. On the other hand all decisions of Member States excluding public service provides from competition rules are subject of review for their compliance with the general principles. So the key question is whether a measure is necessary to achieve legitimate goals of general interest or whether it goes further than that. In the field of Article 106 (2) TFEU the European Court of Justice developed extensive and inconsistent case law. From very restrictive approach allowing only these measures which have been indispensible to achieve SGEI goals to a more flexible interpretation in more recent cases. This paper provides an overview of an interplay between the principle of proportionality and the policy-based measures to create preferential conditions for SGEI operators.